Analyzing Drivers' Attitude towards HUD System Using a Stated Preference Survey. (9th February 2014) - Guo, Hongwei; Zhao, Facheng; Wang, Wuhong; Jiang, Xiaobei
Abstract : It is very important for drivers to obtain driving information easily and efficiently. There are many advanced devices used for driving safety assistance. Of these assistance devices, the head-up display (HUD) system can promote the reduction of driver's reaction time and improve spatial awareness. The drivers' attitude towards and preference for HUD system are crucial to design the functional framework and interface of HUD system. This study explored the relationships between drivers' attitude and HUD presentation image designs using stated preference data from questionnaire survey. The questionnaire included drivers' attitude towards the use of HUD and the preference for the information display zone and information display elements of the HUD. Contrastive analysis was adopted to examine the variations in drivers' attitude and preference for age and driving skills. According to the results, the participants have varying attitudes to HUD system, but most participants show relatively unified preference for the information display zone and information display elements. The results can also be used to customize a HUD presentation image which is in accordance with the drivers' feelings and preferences.